2018
DOI: 10.1080/09637486.2018.1475551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blueberry extract, carriers, and combinations on the growth rate of probiotic and pathogenic bacteria

Abstract: The blueberry is recognised as a source of phenolic compounds that have beneficial effects on human health; however, they possess low bioavailability and can be degraded by gastrointestinal conditions. Encapsulation has been widely used to mitigate these disadvantages; Gum Arabic (GA) and Corn Syrup Solids (CSS) are common carriers used in this technique. The aim of this study was to evaluate the effect of Blueberry Extract (BE), carriers and their mixtures on the kinetic growth and maximal growth rate of prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The probiotic inoculum (1%) was added to the MRS-modified broth mediums and incubated at 37 °C. MRS broth without glucose (MRSm) was used as a negative control [ 13 , 14 ]. The growth rate of bacteria was measured using the Optical density (OD) at 600 nm using Multitask GO UV/VIS spectrophotometer (Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The probiotic inoculum (1%) was added to the MRS-modified broth mediums and incubated at 37 °C. MRS broth without glucose (MRSm) was used as a negative control [ 13 , 14 ]. The growth rate of bacteria was measured using the Optical density (OD) at 600 nm using Multitask GO UV/VIS spectrophotometer (Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The growth rate of bacteria was measured using the Optical density (OD) at 600 nm using Multitask GO UV/VIS spectrophotometer (Thermo Scientific, Waltham, MA, USA). The maximal growth rate (µmax) was estimated by the logistic model using the Software OriginPro2016 (OringinLab Corporation, Northampton, MA, USA) [ 14 ]: where y is the OD in Arbitrary Units (AU), a is the maximal population growth value (AU), k is the intrinsic growth rate (h −1 ), b is a constant that depends on the initial condition, and x is the time (h). Moreover, the maximal growth point was obtained ( t max and OD max ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest growth was observed when EM was administered in the LN microbiota in the TC and DC. Previous research found that anthocyanin, from blueberry extract, with a chemical structure similar to that of deglycosylated flavonoids, stimulated Salmonella typhimurium growth, but after a while, the growth stopped [74]. Others found that an extract rich in aglycone naringenin form naringin inhibited the growth of S. typhimurium; this is one flavonoid present in C. auraintium extract [75].…”
Section: Short-chain Fatty Acid Productionmentioning
confidence: 99%
“…The BPEs and BWPEs were extracted using the method provided by Michel-Barba et al (2018). Blueberry pomace and blueberry wine pomace were dried at 40°C, and then mixed with an ethanol/ water (v: v, 50:50) solution containing the hydrochloric acid (v: v, 0.01%) at a mass-to-volume ratio of 1:40.…”
Section: Extraction Of Active Substances From Blueberry Pomace and Blueberry Wine Pomacementioning
confidence: 99%